Giving Dowry to Women Jasser Auda's Maqashid Syariah Perspective - Meylinda Rosyidah, Meylin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
This article examines Jasser Auda's maqashid sharia perspective on the problems of giving dowries to women. As is generally known, there are many journals or articles that study the standardization of giving dowry to women and the law on giving dowry. Here the researcher wants to examine more deeply about dowry from Jasser Auda's perspective, where it is known that Jasser Auda is a contemporary Muslim intellectual figure in both the Islamic and Western worlds and many of his books discuss maqashid sharia, so the researcher is interested in studying more deeply how the standardization of giving dowry for women according to Jasser Auda's maqashid sharia theory? This problem still gives rise to many differences of opinion, as in the Al-Qur'an, Surah an-Nisa' verses 4 and 20 and Surah al-Baqarah verse 237 which explains about dowry. This research uses qualitative research with a library research approach. The results of this research are that giving dowry to women from the perspective of maqâshid sharia, at least does not burden both parties, in accordance with the objectives of sharia (maqashid sharia), giving dowry does not burden men and does not make dowry matters easier.